Assessment of open spaces related to Riedel-shears dip effect in brittle shear zones. (January 2022) - Kavyani-Sadr, Khashayar; Rahimi, Behnam; Khatib, Mohammad Mahdi; Kim, Young-Seog
Abstract: The cross-cutting of Riedel fractures in brittle strike-slip shear zones creates fault blocks. Open spaces develop between the blocks as they rotate due to increased shear deformation. The present research focuses on extending open spaces vary from one shear zone to others depending on the dip direction of the sub-fractures and the structural styles of the shear zones. The relationship between the amount of shear (γ) and 3D open spaces in brittle shear zones has been examined with the help of analogue modelling and statistical analysis based on the results obtained from the models. The dip direction of R-fractures within a shear zone has been shown to play a crucial role in the creation and the volume of open spaces (VOS). However, its effects differ from a simple shear to transpressive regime. In the former, the VOS was higher when the dip direction of R-fracture planes was synthetic to the shear sense. Furthermore, near-vertical R-fractures showed a tendency to form more space and vice versa. The effect of R′-shear dip angle on the VOS under various shear strains was low, and its influence was restricted to situations affecting the rotation of Riedel blocks. The total positive dilatation in the transpression was higher than that under simple shear. For both deformation settings, most of the open spaces occurred along the R′-fractures. The role of the statistical analysis in this study was to evaluate the predictive power of variables such as shear strain (γ), angle of convergence (α), and R-fractures dip angle (θR ). These parameters were obtained from the modelling and their significant efficacy of dilatation. 10% leave out cross-validation method was used to evaluate the accuracy of the prediction of open spaces. Moreover, 82.5% of the random variations of the open spaces can be accurately predicted by the controlling variables: θR, θR′, α, and γ. Highlights: The dip direction of Riedel-shears affects the volume of open spaces. The dilatation along the R′-shears in transpression is more than simple shear. More spaces are created within Riedel-shears with higher dip angles in simple shear. The volume of open spaces in brittle shear zones can be predicted with a linear model.